(untitled) (e-Journal of Linguistics, 2020)
Second language reading is affected by reading habit of first language, the reading proficiency, the strategies of reading, and reading attitude (Sundari, 2013). The questions lies in this study are (1) how does English reading habit of students with different L1 reading habit, L2 reading proficiency, and reading attitude? (2) And what is the factor mostly affected the English reading habit? This is a qualitative- quantitative research, this is a qualitative research for its purpose to describe the English habit, and this study is also a quantitative research for its purpose to find the most factors affected the English reading habit by applying the formula of correlation to see the highest coefficient correlation. The instruments of this study are two questionnaires of (1) reading attitude by M.N. Gomleksiz (2004) and (2) L2 reading habit by Ro Eunseok and Alice (2014) which are administered to 23 students. The result of this study are: (1) English reading habits of the subjects found out various and different due to the combination of the three factors collaborated, from 23 students there are 11 of them are in low English reading habit, 8 of them are in moderate English reading habit, and 4 of them are in high English reading habit. (2) Though, L1 reading habit is mostly low but L2 reading proficiency is the factor mostly affected English reading habit since its coefficient correlation is the highest 0,76.